KEDUDUKAN HUKUM PANTI ASUHAN SEBAGAI WALI DARI ANAK DIBAWAH UMUR - Sari, Hanita; Sjaifurrachman, Sjaifurrachman; Rofiqi, Imam (2024)
The Civil Code does not allow a legal entity to be the guardian of a minor child, but in other provisions in law regulation no. 35 of 2014 concerning child protection allows for the implementation of guardianship by legal entities. So it is necessary to question the legal position of the orphanage as guardian of minors and the responsibility of the orphanage as guardian of the assets of minors. The purpose of writing this thesis is to describe the legal position of orphanages as guardians of minors and to explain the responsibilities of orphanages as guardians of the assets of minors. The research method used in writing this thesis is to use a normative juridical research type which uses legislation such as the Civil Code and the Child Protection Law as the main reference. The research approach used is the statutory approach. The types and sources of law used are primary legal materials and secondary legal materials. The first discussion concerns the position of an orphanage as guardian of a minor when there is a court order that the orphanage has the right to take care of the child's personal care. Next, the second discussion concerns the responsibilities of orphanages in fulfilling their obligations as guardians of the assets of minor children. It can be concluded that when guardianship is implemented in an orphanage without a court order, the orphanage is only carrying out its role as a child social welfare institution. Regarding responsibility for children's assets, there must be special supervision from an institution so that there is minimal chance of guardians misappropriating children's assets.